SUSTAINABLE VILLAGE: TRANSFORMASI LAHAN TIDUR MELALUI BUDIDAYA CABAI RAMAH LINGKUNGAN - Ipol, Dina Chintamy; Wulansari, Ekawati Rini (Penerbit Widina, Widina Media Utama, 2025)
Efi-Efi Village in South Tobelo District faces major challenges in the form of a large amount of unused, unproductive land and the community's dependence on a single agricultural commodity. This situation has resulted in low household incomes and a decline in the economic well-being of the village community. This community service activity aims to optimize local potential through the